Dlaczego Francuzi odrzucili Europejski Traktat Konstytucyjny? - Karbowska, Monika (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2007)
The Author presents the main elements of the Euroconstitution that have caused the greatest protest of French society and resulted in its rejection in the referendum of May 2005. These include: the ultra-liberal economic system of the EU, poor protection of human rights and the rights of employees, poor security of democratic functioning of the EU structures, subjecting of the EU defense policy to NATO, failure to provide for a secular character of states and insufficient guarantees of women’s rights. The second part of the paper is devoted to the analysis of the activity of French civic society in the constitutional campaign and to the Author’s participation in this campaign.
Why did the French reject the constitution treaty ?